Preparation of ethylcellulose/methylcellulose blends by supercritical antisolvent precipitation - Duarte, Ana Rita C. (2006)
The supercritical antisolvent (SAS) techniquewas used to prepare ethyl cellulose/methyl cellulose blends, two biocompatible polymers commonly used as drug carriers in controlled delivery systems. Ethyl cellulose is widely used as a drug carrier. The drug release of the delivery devices can be controlled to some extent by addition of a water-soluble or water swellable polymer, such as methyl cellulose. This leads to the solubility enhancement of poorly water-soluble molecules. SAS experiments were carried out at different operational conditions and microspheres with mean diameters ranging from 5 to 30 m were obtained. The effect of CO2 and liquid flow, temperature and pressure on particle size and particle size distribution was evaluated. The microspheres were precipitated from a mixture of dichloromethane (DCM) and dimethylsulfoxide (DMSO) (4:1 ratio). The best process conditions for this mixture were according to our study 40 ◦C and 80 bar.